Lifeguard turnover in aquatic and recreation centres: Perspectives from managers. (April 2021) - Butson, Michael; Tower, John; Schwarz, Eric C
Employee turnover is the loss of talent in the workforce. High employee turnover is expensive and disruptive. Young employees are more likely to leave one job for a better one and are often less attached to an organisation while they are completing their education. The aquatics industry has been described as being in a crisis, experiencing unprecedented levels of turnover amongst lifeguards. A first important step is to understand the reasons for turnover amongst lifeguards. This study utilised semi-structured interviews with aquatic and recreation centre managers (N = 16; 69% female) to explore their insights about lifeguard turnover. A deductive content analysis determined that lifeguards leave their current position for four main reasons: lifeguarding being a temporary position, a negative working environment, pursuing employment in a higher paying lifeguard position and location. Consequently, centre managers need to consider short and long-term strategies to retain lifeguards.